1992
DOI: 10.1007/bf00194869
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipids and polysaccharides during pollen ontogeny in Oenothera anthers

Abstract: Sudan B and PAS reactions were used for the histochemical detection of lipids and polysaccharides with light microscopy in semithin slides of resin-embedded Oenothera hookeri De Vries a anthers at different ontogenic stages. The aim was to establish the variations that occur in both kinds of metabolic products during normal pollen development.In reproductive cells a wave of amylolysis/amylogenesis is observed simultaneously with a lipidic wave. Starch in diploid PMCs is different from starch in the haploid veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In different species (Keijzer 1987;Noher de Halac et al 1992) the processes were similar to those described here for D. racinae, T. aeranthos and A. recurvata, although the time at which they occur is similar only for the first two species. In A. recurvata the same processes occurs relatively late.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…In different species (Keijzer 1987;Noher de Halac et al 1992) the processes were similar to those described here for D. racinae, T. aeranthos and A. recurvata, although the time at which they occur is similar only for the first two species. In A. recurvata the same processes occurs relatively late.…”
Section: Resultssupporting
confidence: 74%
“…It was described that in Tillandsia pallidoflavens (Hess 1991) and in Lilium henryi (Dickinson 1981), the plastids in the archesporial cells accumulate polysaccharides. In Smilax aspera (Pacini & Franchi 1983), in Lilium longiflorum (Miki-Hirosige & Nakamura 1983) and in Oenothera hookeri (Noher de Halac et al 1992), the occurrence of starch grains in the microspore mother cells was described. An analysis of the literature showed that there is variability in this aspect, including species of a same genus as in Lilium (Dickinson 1981;Clément et al 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Monocots such as Tilloridsin pnllirloflnvescetis (Hess 1991), Ophtys liiren (Feijo & Pais 1988). L d i r i t r~ pereririe (Pacini et al 1992a) and Pterostylis plirriiosn (Pandolfi et al 1993) have only one stage of differentiation, more precisely amylogenesis, during development, whereas species such as Sri~ilnr aspern, have three amylogeneses (Pacini & Franchi 1983 , whereas Oerrotliera liookeri has only one (Noher de Halac et al 1992). Irrespective of the number of amylogeneses, mature pollen grains may or may not contain starch ; moreover, in species such as Pnrietarirr jrmdnicn, the percentage of grains containing starch varies in relation to the season (Franchi et al 1984).…”
mentioning
confidence: 99%